'It's Complicated': Canadian Correctional Officer Recruits' Interpretations of Issues Relating to the Presence of Transgender Prisoners. Issue 1 (13th February 2020) - RICCIARDELLI, ROSEMARY; PHOENIX, JO; GACEK, JAMES
Abstract: Drawing upon semi‐structured interviews with correctional officer recruits in training (n = 55), we reflect on recruit interpretations of transgender (trans) prisoner placement within federal prisons in light of recent changes instigated by Canadian Prime Minister Trudeau. Recognising that prison is a carceral and gender binary space, we assert that trans prisoner lives and experiences cannot easily be appropriately recognised or included in prison policy and prisoner management procedures. Our findings reveal that most recruits are supportive and appreciative of the complexities of trans experiences, yet some, especially those with prior experience working in prisons, describe occupational strains tied to accommodating trans prisoners.